Nanosizing Ammonia Borane with Nickel: A Path toward the Direct Hydrogen Release and Uptake of BNH Systems. (27th December 2017) - Lai, Qiwen; Rawal, Aditya; Quadir, Md Zakaria; Cazorla, Claudio; Demirci, Umit B.; Aguey‐Zinsou, Kondo‐Francois
Abstract: Ammonia borane (AB), with one of the highest hydrogen content (19.6 mass%), has attracted much attention as a potential hydrogen storage material. However, its complex and multistep thermal decomposition process has left the idea that AB can only be an irreversible hydrogen storage material. Herein, we demonstrate the potential of a novel nanosizing strategy in overcoming current drawbacks. By (a) successfully restricting the particle size of AB to the nanoscale (≈50 nm), and (b) discreetly encapsulating the synthesised nanosized AB particles within a nickel (Ni) matrix, AB showed unforeseen hydrogen reversibility along its decomposition path. Owing to the catalytic effect of Ni and the embedment of AB with the Ni matrix, this nanosizing approach reduced the hydrogen release temperature, suppressed the melting of AB and the production of volatiles by‐products including diborane and borazine. But more remarkably, this approach enabled the reversible release and uptake of pure hydrogen at 200 °C and 6 MPa H2 pressure, only. Reversibility is thought to occur through an iminoborane oligomer resulting from the initial decomposition of the nanosized AB/Ni matrix. This result demonstrates for the first time the possibility of tailoring. Abstract : Ammonia borane (AB), with one of the highest hydrogen content (19.6 mass%) of known materials, is often regarded as an irreversible hydrogen storage material. Nanosizing AB and further coating with nanosized nickel (Ni) leads to a AB/Ni matrix that enables hydrogen reversibility along the thermal decomposition path of AB.